Justification and selection of a method for restricting water inflow to horizontal wells in low-permeability terrigenous reservoir conditions using the example of the YuS2 formation of an oil and gas condensate field - Olga V. Savenok; Nailya Kh. Zharikova; Elizaveta P. Chuykova; Alexander E. Verisokin; Mahmoud Hadid; Larisa V. Povarova; Denis S. Kalashnikov; Anna S. Domanova (Известия Томского политехнического университета: Инжиниринг георесурсов)
Relevance. Today, most of the fields exploited in the Russian Federation have moved to the final stage of development, which entails an inevitable increase in the number of factors complicating hydrocarbon production. One of these factors is the increased water cut of the extracted products. This problem is the cause of increase in specific energy consumption for liquid production, growth of the cost of separating oil and water in the collection and treatment system, as well as increase in the number of equipment failures due to corrosion, deposition of mineral salts and the formation of persistent oil-water emulsions. In many fields, the level of water cut in products already reaches 98–99%, which is the limit of profitability of production and requires the adoption of measures aimed at reducing the share of produced water. Costs become an order of magnitude higher when it comes to horizontal wells, due to the higher complexity and cost of the work carried out on them. Aim. To increase the efficiency of water isolation work in horizontal production wells by determining the most suitable chemical composition to limit water inflow, which would meet the requirements and be available in large quantities to a wide range of domestic oil and gas companies. Objects. The analysis of measures to reduce the water cut of well products. Subject. Various chemical reagents for isolating water inflow and methods for determining the suitability of a well for water isolation work. Methods. General scientific methods (analysis, generalization, synthesis, classification) and specific scientific ones (mathematical modeling, software modeling). The set and combination of these methods are adequate to the goals and objectives, object and subject of research of this work. Results. The authors have carried out a study to improve the efficiency of horizontal wells in conditions of increased water cut of produced products. Based on the research the most effective method of limiting water inflow – the use of gel-forming compositions – was determined. Modelling of polymer flooding was carried out in the tNavigator software package and two development scenarios were compared. The authors developed the methodology for selecting candidate wells for waterproofing work, implemented in the form of a computer program written in the Python programming language.